BIBLIOMETRIC ANALYSIS: FACTORS CAUSING AND PREVENTION STRATEGIES FOR BURNOUT IN THE WORKPLACE - Lau Go’o, Maria Alni; Mujanah, Siti; Alif Fianto, Achmad Yanu (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Every individual undoubtedly possesses different physical abilities and psychological conditions, especially when facing life situations, whether it is work-related or in other contexts. A challenging situation or condition can make someone feel pressured and experience prolonged stress if not handled properly. This physical, emotional, and mental exhaustion is known as burnout. This study discusses burnout, which has been addressed in previous research from 2018 to 2023. The method used in this research is to identify the number of journals using Harzing’s Publish or Perish software, as well as bibliometric analysis using VOSviewer. The research results show that there are 200 publications with 60,448 citations and 10,074.67 citations per year discussing burnout. There are eight main clusters based on the bibliometric analysis. This article also provides information on research topics that have not been widely explored, thus offering benefits to future researchers interested in discussing burnout.